FOSTERING STUDENTS’ CREATIVE PROBLEM-SOLVING SKILLS IN MATHEMATICS THROUGH GENERATIVE ARTIFICIAL INTELLIGENCE TOOLS - KALANDAROV UTKIR (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The rapid advancement of digital transformation processes and the integration of generative artificial intelligence (AI) technologies into education are creating new opportunities for improving the content and methodology of mathematics education. In particular, generative AI tools such as ChatGPT, Gemini, Claude, and Copilot expand students’ opportunities to engage in independent thinking, develop multiple solution strategies, and demonstrate creative approaches while solving mathematical problems. Contemporary research indicates that, alongside its positive impact on learning outcomes, the effective implementation of generative AI requires the development of appropriate pedagogical mechanisms and instructional frameworks. This article analyzes the theoretical and pedagogical foundations for fostering students’ creative approaches to solving mathematical problems through the use of generative AI tools and proposes an innovative methodological model aimed at enhancing creative problem-solving competencies in mathematics education.